Hydrochemical evaluation of water quality and its influencing factors in a closed inland lake basin of Northern China - Ren, Xiaohui; Yu, Ruihong; Kang, Jianfang; Li, Xiangwei; Wang, Rui; Zhuang, Shuai; Wang, Dalun; Zhang, Xiangyu (Frontiers in Ecology and Evolution, 2022)
Understanding the water quality and its influencing factors of different water bodies is essential for managing water resources in closed inland lake basins in semi-arid regions. However, generally, groundwater or surface water is assessed separately, and the differences among different water bodies are neglected. This study assessed the water quality and its influencing factors of different water bodies in the Daihai Lake Basin (a closed inland lake basin in a semi-arid region) by analysing the hydrochemical data of groundwater, and spring, river, and lake waters in the dry and wet seasons. The dominant hydrochemical type of groundwater (81.48%), spring water (80%), and river water (83.33%) was HCO3-Ca•Mg, while that of lake water was Cl-Na (100%). Groundwater, spring water, and river water were suitable for drinking and agricultural irrigation; however, the groundwater quality was worse in the wet season than in the dry season. Na+ and Cl- majorly affected the lake water quality. The mean NO3- concentration in groundwater was 28.39 mg/L, and its non-carcinogenic hazard quotient indicated that high risk areas were mainly distributed in Tiancheng and northern Maihutu. The hydrochemical compositions of groundwater, spring water, and river water were mainly influenced by rock (silicate and carbonate) weathering and cation exchange, and agricultural activities were the main sources of groundwater NO3-. Moreover, the lake hydrochemical composition was mainly affected by evaporation and halite dissolution. Thus, groundwater NO3- pollution and lake water salinisation should be prioritised.These findings provide a more thorough understanding of water quality and its influencing factors in the closed inland lake basin in the semi-arid region, and can be used to develop the protection of ecosystems and water resources management strategies in the Daihai Lake Basin.